Reifying discrimination on the path to school leadership: Black female principals’ experiences of district hiring/promotion practices - Weiner, Jennie; Garrett-Walker, Whitnee; Strickland, Taylor; Burton, Laura (Frontiers in Education, 2022)
Using intersectionality as a guiding framework, this qualitative study focuses on the hiring/promotion experiences of 20 Black female principals and explores how their hiring/promotion practices reified and/or interrupted traditional discriminatory pathways to school leadership. We find that gendered racism operated across all facets of the principal recruitment and hiring processes in which these women participated. First, relationships and political connections with those already in power (e.g, predominately White men) seemed to be a key mechanism for entering the applicant pool and, later, accessing leadership opportunities. Opportunities were often explicitly racialized such that considerations for leadership positions were stated as being based on the participants being Black. Second, interview processes were frequently described as more performative than substantive with many of the women highlighting questions and comments that reinforced problematic tropes about Black women. Questions also abounded about whether interview panels were reflective of the community and/or if the questions were standardized to ensure fairness and transparency. Finally, district level hiring decisions were frequently disconnected from the interview process and lacked transparency with superintendents, in particular, who overrode or ignored prior steps in, or recommendation from, the school-based part of the process. In this way, findings suggest a hiring/promotion system desperately in need of revision starting with the most basic design features (e.g., standardized interview questions, transparent performance indicators, process accountability via decision-making) and including disrupting discrimination across all facets of the system.